2018
DOI: 10.1007/s00330-018-5452-9
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Reference ranges of left ventricular structure and function assessed by contrast-enhanced cardiac MR and changes related to ageing and hypertension in a population-based study

Abstract: The original version of this article, published on 14 March 2018, unfortunately contained a mistake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…For example, a CMR study by Lei et al (13) demonstrated that there was no significant correlation between EF and age. In contrast, we confirmed that both LVEF and RVEF were increasing with age, which was consistent with several previous studies (12,20,21,36). In addition, the relationship between physiological aging and LVM has long been quite controversial.…”
Section: Discussionsupporting
confidence: 93%
“…For example, a CMR study by Lei et al (13) demonstrated that there was no significant correlation between EF and age. In contrast, we confirmed that both LVEF and RVEF were increasing with age, which was consistent with several previous studies (12,20,21,36). In addition, the relationship between physiological aging and LVM has long been quite controversial.…”
Section: Discussionsupporting
confidence: 93%